Coping with diversity in classrooms: predicting Intercultural Self-Efficacy in mandatory education teachers - Argüello-Gutiérrez, Catalina; Smith-Castro, Vanessa; Martín-Gutiérrez, Ángela (Social Psychology Education, 2025)
The social integration of immigrants into educational settings is an important challenge for host societies. In this context, teaching skills for managing multiculturalism in the classroom are becoming increasingly necessary. Even though several studies have discussed the role of Self-Efficacy in teacher management, only a few have addressed the specific component of teachers' intercultural Self-Efficacy. The present study analyzed the relative contribution of sociodemographic, occupational, and psychosocial variables in predicting the variance of the Intercultural Self-Efficacy of active teachers throughout Spain. Participants were active teachers from different educational levels (n = 435). A self-administered online questionnaire was used to measure sociodemographic (sex and age), occupational (teaching experience and training in multicultural education), and psychosocial variables (Pro-Diversity Beliefs, Intercultural Sensitivity, Stereotypical Attributions about migration, Acculturation Expectations, and Intercultural Self Efficacy). Results showed that the main predictors of Intercultural Self-Efficacy were age (the older, the higher the Self-Efficacy), having had some training in intercultural competencies, possessing high Intercultural Sensitivity, professing Pro-Diversity Beliefs, and having positive expectations that migrants can maintain their culture (Cultural Preservation Expectation). The results are discussed, considering the need to promote teacher training in intercultural competencies for the better management of cultural diversity in the classroom.
Keywords: teachers; intercultural self-Efficacy; interculturality; immigration